Currency Crisis in South Sudan: Contexts, Causes and Policy Options - Atem, Gabriel Garang (Archives of Business Research, 2022)
This study combines contextual framework, review of South Sudan elites’ speculative policies and empirical evidence between July 2011 to December 2017 to explain the causes of the exchange rate crisis in South Sudan. The study finds elites’ speculative policies and a surging money supply caused the depreciation of the exchange rate. The study argues that policymakers implemented unsustainable policies, and speculative regulations in the financial sector as conduits for the elites to benefit through rent-seeking. Disabled by ineffective monetary and exchange rate transmission channels, the Bank of South Sudan signaled its inability to defend the fixed exchange rate in November 2013 by devaluing the pound. Politics came in the way, the devaluation was rescinded by parliament in December 2013. The devaluation was later implemented in December 2015 at a higher exchange rate when the Bank of South Sudan surrendered to defending a fixed exchange rate regime. South Sudan’s macroeconomic environment is characterized by hyperinflation, depreciation and lack of political will to ensure good economic governance prevails. Resolving macroeconomic challenges of such magnitude, requires external policy and financial support for the Bank of South Sudan to correct the exchange rate and monetary policy challenges.